The Implementation of Think Pair Share Assisted with Pop Up Media Increases Students’ Outcomes - Yenni Oktaviani; Erik Aditia Ismaya; Eko Widianto (Jurnal Ilmiah Sekolah Dasar, 2020)
In current learning, teachers still use the lecture method and rarely use media to support learning so that students feel bored and less enthusiastic about participating in learning activities resulting in low student learning outcomes. This study aims to analyze the improvement of student learning outcomes in the realm of knowledge and skills using the think pair share learning model assisted by pop-up media in class V. This type of research is classroom action research. This study consisted of 4 stages, namely planning, acting, observing, and reflecting. The research subjects were 23 students in grade V. Data collection techniques in this study were test and non-test. The data analysis technique used quantitative and qualitative data analysis techniques. The results of this study indicate that the learning outcomes of students in the domain of social science content knowledge in the first cycle obtained an average value of 69 and the Indonesian language content obtained an average value of 70 while in the second cycle the social studies content obtained an average value of 79 and the Indonesian language content obtained an average value. -averaged 80. The results of learning skills in the first cycle obtained an average score of 66 in the category of needing guidance while in the second cycle an average score of 78 was in the sufficient category. Based on the research results, it can be concluded that applying the think pair share learning model assisted by pop up media can improve learning outcomes in class V.